Green Marketing Mix and Environmental Knowledge: Shaping Gen Z and Millennials’ Sustainable Furniture Intentions - Soepatini, Soepatini; Putra , Bintang Kharisma; Suryandari , Rullynta Siska; Kuswati, Rini (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study investigates how Indonesian Gen Z and millennials’ purchase intentions for green furniture from Ace Hardware, IKEA, Informa, KANA Furniture, and Uwitan are shaped by the green marketing mix—product, price, place, and promotion. Its academic contribution lies in integrating environmental knowledge as a boundary condition into the marketing mix framework while embedding a skepticism-based perspective, thereby clarifying when specific green signals succeed or fail. A quantitative survey of 256 respondents was analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS. Findings indicate that green promotion, place, and price significantly influence purchase intentions, whereas green product does not. Environmental knowledge moderates the link between green product and place, suggesting its importance in sustainable consumption. This study advances green marketing scholarship by addressing the tension between persuasion and skepticism. Practically, it guides firms to build credibility and communicate sustainability initiatives more effectively to young consumers in emerging markets.